A STUDY ON ADVANCE JAVA WITH DATABASE MANAGEMENT - JATIWAL , MONIKA; ARORA, CHETNA; ARORA, CHARU (IJRDO -Journal of Computer Science Engineering, 2015)
This paper gives a short description about the java and databaseconnectivity. It describes the advance java features with databaseconnectivity. It also describes the application programming interface withapplets and swings. This paper explains about the java and its connectivity with database. It describes the structured query language as a datadefinition and data manipulation language. It also defines the java platform.